ARCHETYPAL CHARACTERS IN BEAUTIFUL BOXER AND WHITE CHICKS FILMS - Stefanus, Briananda; Sili, Surya; Nasrullah, Nasrullah (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2020)
The concern of this study was about the archetypal characters of men characters who transformed into women as portrayed by Toom of Beautiful Boxer and Kevin & Marcus of White Chicks films. This study used Jung’s four major archetypes to find out the types of archetype portrayed by the three men characters and their similarities and differences toward each other. Qualitative research was the research design of this study. The data used in this study were words (narrations and dialogues) related to Toom character taken from the English Subtitle of Beautiful Boxer film and Kevin & Marcus characters of White Chicks film script. This study found the archetypes portrayed by Toom of Beautiful Boxer film were persona, shadow, and anima. Meanwhile, the archetypes of persona and anima were portrayed by Kevin and Marcus of White Chicks film. The similarity of archetype portrayed by Toom, Kevin, and Marcus was that their anima archetype existing from another archetype which led to the difference among the three of them. Toom’s anima was the result of his growing shadow containing his oppressed desire of becoming a real woman, while Kevin and Marcus’ anima came from their persona archetype related to their mission of pretending as women. Based on these findings, this study concluded that shadow archetype affected Toom’s decision of transforming into woman, while persona affected Kevin and Marcus’.